Radiological and Anatomical Evaluation of the Tracheal Morphology and Morphometry in Turkish Adults/Evaluacion Radiologica y Anatomica de la Morfologia y Morfometria Traqueal en Adultos Turcos - Polat, Sema; Oksuzler, Mahmut; Oksuzler, Fatma Yasemin; Ozsahin, Esin; Goker, Pinar (International journal of morphology, 2023)
The trachea is a tubular organ lying between larynx and lungs containing smooth muscle, membranes, and cartilage. This paper evaluated the dimessions of the trachea and main bronchi morphometry in healthy adults using Computed Tomography. This retrospective observational study was performed with 170 healthy adult subjects (89 females, 52.35 %; 81 males,47.65 %). The length of the trachea, the anteroposterior and transverse diameter of the trachea and the right and left main bronchi were measured. From these measurements, the trachea shape were calculated and four types of trachea were identified as circular, oval, horseshoe-shaped, and rectangular. All measurements were significantly higher in males than females (excluding tracheal bifurcation angle). According to the value obtained by dividing the anteroposterior by the width of the trachea, tracheal shapes are considered; the circular shape was seen 104 subjects (61.2 %), followed by oval type (34 subjects), horseshoe type (24 subjects) and rectangular type.(8 subjects). Also, the most frequently seen was circular type in both females and males. Hovewer, there was no significant difference between sex in terms of trachea shape. Additionally, a striking finding was that trachea morphometry and morphology showed the significance according to age dependent changes. Trachea measurements were affected several reasons such as used methods, age, sex, or race. This study has many clinical importance as it may reduce the risk of accidental damage to these area by clinicians such as cardiothoracic surgeons, anesthetist, or radiologist. KEY WORDS: Trachea length; Age and sex-related changes; Trachea shapes; Morphometry.